Blonanserin ameliorates social deficit through dopamine-D3 receptor antagonism in mice administered phencyclidine as an animal model of schizophrenia. (September 2019) - Takeuchi, Saori; Hida, Hirotake; Uchida, Mizuki; Naruse, Ryo; Yoshimi, Akira; Kitagaki, Shinji; Ozaki, Norio; Noda, Yukihiro
Abstract: Blonanserin differs from other antipsychotic drugs, such as risperidone and olanzapine, and exhibits a higher affinity for dopamine-D2/3 receptors than for serotonin 5-HT2A receptors. We investigated the involvement of dopamine-D3 receptors in the effect of blonanserin on the social deficit observed in an animal model of schizophrenia and sought to elucidate the molecular mechanism underlying its action. Mice received phencyclidine (PCP: 10 mg/kg/day, s.c.), a non-competitive N -methyl-d -aspartate (NMDA) receptor antagonist, once a day for 14 consecutive days. We then evaluated the sociability, using a social interaction test, and the expression of GluN1 subunit, an essential subunit of the NMDA receptors, in these mice. Blonanserin significantly ameliorated the PCP-induced social deficit, whereas olanzapine and haloperidol did not. This effect of blonanserin was antagonized by 7-OH-DPAT, a dopamine-D3 receptor agonist, and SCH23390, a dopamine-D1 receptor antagonist. However, the ameliorating effect of blonanserin was not inhibited by DOI, a serotonin 5-HT2A receptor agonist. The PCP-induced social deficit was also ameliorated by U99194, a dopamine-D3 receptor antagonist and SKF38393, a dopamine-D1 receptor agonist, being effects antagonized by 7-OH-DPAT or SCH23390. Blonanserin significantly inhibited the decrease in the phosphorylation levels of GluN1 at Ser 897 by protein kinase A (PKA) in the prefrontal cortex (PFC) in PCPadministered mice. These results suggest that activation of NMDA receptors due to Ser 897 -phosphorylation of GluN1 subunit, which is a step linked to dopamine-D1 receptor-PKA signaling through dopamine-D3 receptor antagonism in the PFC, is required for the ameliorating effect of blonanserin on the PCP-induced social deficit. These findings also provide in vivo evidence that blonanserin antagonism of the dopamine-D3 receptors may be useful as a novel treatment strategy and that the dopamine-D3 receptors can be a novel therapeutic target molecule for the social deficit observed in schizophrenia. Highlights: Blonanserin ameliorated phencyclidine-induced social deficit. Ameliorating effect was mediated via dopamine-D3 receptor antagonism. Dopamine-D3 receptor antagonism augmented dopaminergic neurotransmission. The effect was due to functional activation of dopamine-D1 -NMDA receptor pathway.